2020
DOI: 10.1080/03670244.2020.1858408
|View full text |Cite
|
Sign up to set email alerts
|

Rural Midwestern Mexican Fathers’ Perspectives on Family Food, Mealtimes, and Physical Activity

Abstract: Two focus group interviews with eight low-income Mexican fathers in two communities in a rural Midwestern state explored fathers' perceptions, behaviors, and roles related to child and family food consumption, mealtimes, and physical activity. On average, fathers were 34 years of age, had 10 years of formal education, and annual household incomes ranged from $36,250 to $46,249. Findings include the identification of fifteen themes through the process of thematic analysis that are organized by five thematic are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 46 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…In addition, parents identified time constraints along with unsafe neighborhood streets and parks as major challenges to being active as a family. These findings are consistent with previous research, suggesting that lack of time and unsafe environments are the reported barriers to PA among Hispanic families [ 15 , 17 , 42 ]. Furthermore, these findings highlight the importance of providing Hispanic families with (a) PA that requires short bouts of time, which are effective in increasing PA in adults and children at home [ 43 ], and (b) tips on how to be active at home after school during weekdays and on weekends.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, parents identified time constraints along with unsafe neighborhood streets and parks as major challenges to being active as a family. These findings are consistent with previous research, suggesting that lack of time and unsafe environments are the reported barriers to PA among Hispanic families [ 15 , 17 , 42 ]. Furthermore, these findings highlight the importance of providing Hispanic families with (a) PA that requires short bouts of time, which are effective in increasing PA in adults and children at home [ 43 ], and (b) tips on how to be active at home after school during weekdays and on weekends.…”
Section: Discussionsupporting
confidence: 93%
“…Sixteen studies conducted across North America [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ], Europe [ 50 , 51 , 52 , 53 ] and Australia [ 54 , 55 , 56 , 57 ] were included in this metasynthesis. Sample sizes ranged from 8 participants [ 40 ] to 149 participants [ 47 ], with studies exploring the perspectives of fathers, mothers and families. Semi-structured interviews and focus groups were used for data collection and thematic analysis was a preferred method for data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The first environmental influence was fathers’ collaboration with their families. Collaboration was defined across studies as the combined efforts of the family to complete meal-related tasks [ 40 , 42 , 46 , 49 , 51 , 53 , 54 , 55 , 56 , 57 ]. In the presence of disagreement, families who did not collaborate appeared to experience prolonged exposure to mealtime conflict.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent research found that moth-ers were more likely to report improvements in relationships with their children during the pandemic than fathers [43], which may be a reflection of the greater amount of time spent with them. Future research may want to specifically examine fathers' perspectives during the pandemic, as research points to the role fathers also play in shaping children's health behaviors around food (e.g., see [44,45]). Similarly, a study that combines parent and child perspectives may provide additional useful information about how children perceive changes in the food environment during chronic stressful periods and how those align with parent perspectives.…”
Section: Strengths and Limitationsmentioning
confidence: 99%